NZ J Ecol 2018
DOI: 10.20417/nzjecol.42.18
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand forest dynamics: a review of past and present vegetation responses to disturbance, and development of conceptual forest models

Abstract: New Zealand forests have been and are shaped by a suite of disturbance types that vary in both their spatial extent and frequency of recurrence. Post-disturbance forest dynamics can be complex, non-linear, and involve multiple potential pathways depending on the nature of a perturbation, site conditions, and history. To capture the full range of spatial and temporal dynamics that shape forest ecosystems in a given area, we need to use and synthesise data sources that collectively capture all the relevant space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 114 publications
(152 reference statements)
0
17
0
Order By: Relevance
“…, 2010; Richardson et al , 2014; Wilmshurst et al. , 2014; Wyse et al , 2018). We found that in the central and western areas of the site, tree species had failed to regain their previous degree of dominance, with herbaceous, fern, and, to a lesser degree, shrub species remaining more abundant.…”
Section: Discussionmentioning
confidence: 99%
“…, 2010; Richardson et al , 2014; Wilmshurst et al. , 2014; Wyse et al , 2018). We found that in the central and western areas of the site, tree species had failed to regain their previous degree of dominance, with herbaceous, fern, and, to a lesser degree, shrub species remaining more abundant.…”
Section: Discussionmentioning
confidence: 99%
“…If conditions change, however, the outcome may change (Seidl et al 2011). Disturbance, in particular, can have a major impact on succession (Allen et al 2013;Wyse et al 2018). It is inevitable that disturbance will occur (e.g.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Tree fern trunks provide suitable establishment surfaces for epiphytes and hemiepiphytes, and surfaces for climbers to attach to (Pope 1926;Ashton 2000;Rivière et al 2008;Gianoli 2015). Other than Weinmannia-tree fern communities (Wyse et al 2018), however, the density of epiphytic establishment on tree ferns in the understorey is low, so damage from woody epiphytes may not be a significant risk for individual tree fern survival (Brock & Burns 2021;Veblen & Stewart 1980;Gaxiola et al 2008). Furthermore, although some species of epiphyte frequently establish close to the growing crown (e.g.…”
Section: Introductionmentioning
confidence: 99%